Nanoscaled semiconductor-on-insulator materials, sensors and devices : selected, peer reviewed papers from the 6th International Workshop on Semiconductor-on-Insulator Materials and Devices, 24-28 October, 2010 Kyiv, Ukraine - International Workshop on Semiconductor-on-Insulator Materials and Devices (6th : 2010 : Kiev, Ukraine) 527599; Nazarov, Alexei N.; Raskin, J.-P. (Jean-Pierre), 1971- 527600 (Durnten-Zurich, Switzerland : Trans Tech Publications ; Enfield, NH : Distributed in the Americas by Trans Tech Publications)
Includes bibliographical references and index